Membangun Masyarakat Cerdas “Membaca Untuk Masa Depan Pada Anak Usia Dini” - Ria Efkelin; Ernawati Ernawati; Astrid Komala Dewi; Catherine Hermawan Salim (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
The community service activity entitled "Building a Smart Society: Reading for the Future" The community service activity entitled "Building a Smart Society: Reading for the Future in Early Childhood" aims to increase children's interest in reading and strengthen the role of parents and teachers in fostering a culture of literacy from an early age. The background of this activity is the low interest in reading among Indonesian children caused by a lack of access to reading materials, minimal guidance from parents, and increasing dependence on gadgets. Through this program, it is hoped that parents and teachers will be able to understand the importance of guiding children in fun, interactive, and continuous reading activities. The implementation method of the activity includes lectures, discussions, questions and answers, and observations, involving teachers and parents of early childhood children in the Mangga Dua Selatan RPTRA environment. Evaluation was carried out using pre-tests and post-tests to measure the increase in participants' knowledge. The results of the activity showed an increase in the average score of participants from 59.5 to 84.5 with an N-Gain Score of 0.6 which is included in the moderate category. This proves that the activity is quite effective in improving parents' ability to guide children in reading. This community service activity contributes positively to building awareness of the importance of family literacy as the main foundation for the formation of the next generation. intelligent and competitive. This program is expected to continue to be implemented sustainably to strengthen the reading culture in the community.